REAKSI PASAR MODAL INDONESIA TERHADAP PEMILU PRESIDEN AMERIKA SERIKAT TAHUN 2020 - Setya Ayu Rahmawati; Aji Anggoro (TEMA, 2022)
The 2020 United States Presidential election is a political event that has received widespread attention worldwide. The United States is one of the countries that can affect the stock market returns and volatility in other countries. The objective of this study was to analyze Indonesia’s capital market reaction to the events of the 2020 United States Presidential Election as measured by comparing the difference in the AAR and ATVA before and after the event. This study was conducted using an event study approach on companies that are included in the IDX80 index from the period of February - July 2020. The purposive sampling method was used with a total sample of 79 companies. This study was used data analysis technique in the form of one sample test with a window period of 7 days. The results of the study showed that: (1) There was no significant difference in the AAR on the stocks included in the IDX80 index before and after the events of the 2020 United States Presidential Election. Whereas (2) there was a significant difference in the ATVA on the stocks included in the IDX80 index before and after the events of the 2020 United States Presidential Election.